Odpowiedzi

2009-11-29T19:18:00+01:00
A)
8z-10z-12+7z-4=5z-16
rozwiazanie: 3,75-16=12,25
b)
4p-16-2p²+25p²-p=3p+23p²-16
rozwiazanie: 1,5+5,75-16=-8,75
c)
(x+y)-(x-y)=2y
rozwiazanie: 2*-0,5=-1
2009-11-29T19:25:41+01:00
A) 8z-2(5z+6)+7z-4=8z-10z+6z+7z-4=11z-4
11*3\4-4=8.25-4=4.25
b) 4p-2(8-p do potęgi 2)+5p do potęgi 2-p=4p-16+2p do potęgi 2 +5p do potęgi 2=4p-16+7p do potęgi 2 = 4*1\2 - 16 + 7*(1\2)do potęgi 2 = 2-16+7*1/4 = 2-16+1,75 = (-12,25)
c) (x+y)-(x-y) = x+y-x+y = 2y
2*-0,5 = 1
2009-11-29T19:28:44+01:00
A) 8z -2(5z +6) + 7z = 8z -10z -12 +7z -4 = 5z - 16
dla z = 3/4
5z - 16 =5*(3/4) -16 = 15/4 -16 = 3,75 - 16 = - 12,25
b)
4p -2(8 - p²) +5p² - p = 4p -16 +2p²+5p² - p = 7p² +3p -16
dla p = 1/2
7*(1/2)² + 3 *(1/2) -16 = 7*(1/4) + 3/2 -16 =7/4 + 6/4 - 16 =
=13/4 -16 = 3,25 -16 = - 12,75
c)
(x+y)(x -y) =x² - y²
dla x =0,75 oraz y = -0,5
(0,75)² - (-0,5)² = 0,5625 -0,25 = 0,3125
lub
(x +y) - ( x - y ) = 2y
2*(-0,5) = -1